2001
DOI: 10.1109/49.924878
|View full text |Cite
|
Sign up to set email alerts
|

Design, analysis, and performance evaluation for BICM-ID with square QAM constellations in Rayleigh fading channels

Abstract: We consider bit-interleaved coded modulation with iterative decoding (BICM-ID) for bandwidth-efficient transmission over Rayleigh fading channels. We propose the design criteria that utilize a large Hamming distance inherited in a low-rate code and a new labeling technique designed specifically for fading channels. This results in large coding gain over noniterative coded modulation and performance close to that of "turbo" coded modulation with less complexity. We also show that BICM-ID designed for fading cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
265
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 334 publications
(270 citation statements)
references
References 24 publications
5
265
0
Order By: Relevance
“…This allows a coded modulation system with moderate complexity to have large diversity order and achieve coding gain in fading environments [2]. Furthermore, in [3], [4] it was shown that iterative decoding (ID) can increase the minimum intersignal Euclidean distance of bit interleaved coded modulation (BICM), while retaining the desirable Hamming distance. SSD can provide performance improvement over fading channels by maximizing the diversity of a communication system [1].…”
Section: Introductionmentioning
confidence: 99%
“…This allows a coded modulation system with moderate complexity to have large diversity order and achieve coding gain in fading environments [2]. Furthermore, in [3], [4] it was shown that iterative decoding (ID) can increase the minimum intersignal Euclidean distance of bit interleaved coded modulation (BICM), while retaining the desirable Hamming distance. SSD can provide performance improvement over fading channels by maximizing the diversity of a communication system [1].…”
Section: Introductionmentioning
confidence: 99%
“…We adopt a simple strategy by treating D in (6) as an independent Gaussian noise. With this strategy, the demapping method used for BICM [9] can be applied here to evaluate (7). At the start, without any information about clpn(x), we simply set c = 0 in (6).…”
Section: B the Elementary Signal Estimator (Ese) Principlementioning
confidence: 99%
“…(iii) Generate the soft estimate of the clipping noise using (9). Steps (i)-(iii) are performed respectively by the soft mapper, IDFT and SC modules in the ESE.…”
Section: The Iterative Processmentioning
confidence: 99%
See 1 more Smart Citation
“…Since bit-interleaved coded modulation with iterative decoding (BICM-ID) was introduced [1,2], there have been many efforts made to analyze the impact of applied signal labeling on the system performance. Some researchers tried moving the position of constellation points for a given modulation order, e.g., [3,4], but in most cases the constellation points were fixed and the research focused on solving a combinatorial problem of associating binary labels with constellation points of well known modulations, like 8-PSK, 16-QAM, and 64-QAM [3,[5][6][7].…”
Section: Introductionmentioning
confidence: 99%